The Role of the P1BS Element Containing Promoter-Driven Genes in Pi Transport and Homeostasis in Plants - Sobkowiak, Lukasz; Bielewicz, Dawid; Małecka, Ewelina; Jakobsen, Iver; Albrechtsen, Merete; Szweykowska-Kulinska, Zofia; Pacak, Andrzej M. (Frontiers in Plant Science, 2012)
Inorganic phosphate (Pi) is an easily accessible form of phosphorus for plants. Plant Pi uptake is usually limited however by slow Pi diffusion through the soil which strongly adsorps phosphate species. Plants have developed mechanisms to increase Pi availability. There are also abiotic (phosphate level) and biotic (e.g., mycorrhizal) factors regulating the expression of Pi-responsive genes. Transcription factors binding to the promoters of Pi-responsive genes activate different pathways of Pi transport, distribution, and homeostasis maintenance. Pi metabolism involves not only functional proteins but also microRNAs and other non-coding RNAs.